Steady-state Thermal Analysis of Fault-tolerant PMSM During the Open-phase Mode of Operation - Sizonenko, Vitaliy (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2024)
In this paper, the initial outline of lumped-parameter thermal network and steady-state thermal finite element analysis for the fault-tolerant permanent magnet synchronous machine is demonstrated. The calculations show that the faulty operational mode with two open phases leads to substantial overheating of the machine when the need for the constant or overload torque is present. This challenge can be overcome by utilizing the machine’s restricted operating time, with implementing transient thermal finite element analysis. Alternatively, the machine has the option to operate continuously at a reduced torque.
Keywords: Fault-tolerant electrical machine; permanent magnet synchronous machine; PMSM; finite element analysis; FEA; lumped-parameter thermal network; LPTN; thermal calculations